Bulgaria : Fourth Review Under the Stand-By Arrangement and Request for Waiver of Nonobservance of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2007)
This paper discusses key findings of the Fourth Review Under the Stand-By Arrangement for Bulgaria. Performance in 2006 was broadly satisfactory, although structural reform implementation was weaker than expected. Notably, the government postponed until mid-2007 the launching of the electronic business registry, a key business climate measure. The financial system remains well capitalized and profitable with the modest nonperforming loans. The authorities and IMF staff agreed that the credit restraints should lapse and that Basel II should be implemented cautiously.